Historiographical Texts of Contemporaries on the Restoration of the Lithuanian State as the Locus of Expression of the Local Mentality - Petreikis, Tomas (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English]The stories and recollections of rural districts in Panevėžys County of 1927 in the Lithuanian Central State Historical Archives are analysed as a locus of expression of the local mentality. A deep memoir layer of rural district stories has provided different interpretations when assessing the history, background of the restoration of the municipal activities, the enemies and allies of the independence, and comprehending the limits of own power and actions performed. The aspects of the local mentality reflected in the stories of the rural districts add to the understanding of different assessments of the restoration of the Lithuanian independence in the localities (rural districts).They are aimed at analysing the situation in the specific location in detail and still taking the experiences of people in the rural districts into consideration. Thoughts expressed in the stories of rural districts have often been based on the municipal relevance. The expression of the local patriotism remains the main feature in many descriptions in the stories of rural district municipalities in Panevėžys district. The stories were aimed at convincing the general public that the restoration of the Lithuanian independence was attained through the united forces and that the supporters and principal sponsors were the intellectuals in the rural district municipalities.